Identification and analysis of lncRNA, miRNA and mRNA related to subcutaneous and intramuscular fat in Laiwu pigs - Feng, Hui; Liu, Tianyi; Yousuf, Salsabeel; Zhang, Xiuxiu; Huang, Wanlong; Li, Ai; Xie, Lingli; Miao, Xiangyang (Frontiers in Endocrinology, 2023)
Background Long non-coding RNAs (lncRNAs) regulate adipocyte differentiation and metabolism, However, their function on subcutaneous and intramuscular adipose tissues in pigs is unclear. Intramuscular fat (IMF) is an important indicator for evaluating meat quality. Breeds with high IMF content are often accompanied by high subcutaneous fat (SCF), which severely affects the meat rate of pigs. It is of great significance for porcine breeding to study the mechanism of lncRNA related to adipogenesis and lipid metabolism. Methods We identified differentially expressed lncRNAs, miRNAs and mRNAs in subcutaneous and intramuscular adipose tissues in three female Laiwu pigs by deep RNA-sequencing(|log2foldchange|≥1, P_value ≤ 0.05). The gene expression profiles of IMF and SCF in Laiwu pigs were comparatively analyzed by Bioinformatics methods to identify key lncRNAs, miRNAs, and mRNAs associated with lipid metabolism and adipogenesis. Results A total of 1209 lncRNAs (DElncRNAs), 286 miRNAs (DEmiRNAs), and 1597 mRNAs (DEgenes) were differentially expressed between two types of adipose. Among them, 17 DElncRNAs and 103 target genes play a role in the co-expression network, as well as 59 DElncRNAs, 44 DEmiRNAs, and 88 DEgenes involved in ceRNA network. In GO(Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway analysis of DElncRNAs their target genes involved in many adipogenesis and lipid metabolism biological processes and signaling pathways, such as PPAR signaling pathway, Wnt signaling pathway, MAPK signaling pathway. Conclusions By constructing co-expression and ceRNAs network we found that Wnt signaling pathway play a critical regulatory role in intramuscular adipogenesis and lipid accumulation in Laiwu pigs. TCONS_00006525, TCONS_00046551 and TCONS_00000528 may target WNT5A, WNT10B and FDZ3 in co-expression network, TCONS_00026517 and other lncRNAs regulate the expression of PPARG, RXRG and SCD in ceRNA network, and were involved in Wnt signaling pathway. This study provides a theoretical basis for further understanding the post-transcriptional regulation mechanism of meat quality formation, predicting and treating diseases caused by ectopic fat.